ANALYSIS OF THE METHODS OF DETERMINING THE BRITTLENESS INDEX AND THEIR APPLICATION FOR TERRIGENOUS RESERVOIR ROCKS OF THE DNIPRO-DONETSK BASIN - KRASNIKOVA, Olena; KUZMENKО Pavlo; VYZHVA, Serhii (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article discusses the concept of the rock brittleness index, which is widely used for the design of hydraulic fracturing. Three main approaches to its calculation (mineralogical, using elastic properties, using log data) are characterized. For each of the approaches, the characteristics of the most used calculation methods, which were created for rocks with different mineralogical composition, using different physical properties or based on different empirical dependencies, are given. For two sets of core material samples of terrigenous rocks of the Dnipro-Donetsk Basin, the mineralogical index of fragility according to the main petrogenic components was determined by two different methods and the brittleness index according to elastic properties – Young’s modulus and Poisson’s ratio, the angle of internal friction. A comparative characteristic of the results obtained by different methods was carried out, which showed the similarity of trends in lithology and petrophysical properties of rocks. The authors recommend the Jarvie mineralogical method, which is characterized by high accuracy and ease of use, for use in evaluating terrigenous reservoirs of the Dnipro-Donetsk Basin.